1994
DOI: 10.1007/bf00223640
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific hybridization between common and tepary beans: increased hybrid embryo growth, fertility, and efficiency of hybridization through recurrent and congruity backcrossing

Abstract: Cultivated common bean (Phaseolus vulgaris L.) and tepary bean (Phaseolus acutifolius A. Gray) genotypes possessing desirable agronomic traits were hybridized. The F1 hybrids were backcrossed twice with the common bean (i.e., recurrent backcrossing). Also, alternate backcrosses with common and tepary beans (i.e., congruity backcrossing) were carried out. Embryo culture was necessary for all initial interspecific crosses, and its requirement was proportionally lower when the common bean was used as the recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 19 publications
4
86
0
Order By: Relevance
“…Broughton et al (2003) suggested that molecular markers could be used to help reduce or remove barriers to inter-specific hybridization. Mejía-Jiménez et al (1994) reported that recurrent and congruity backcrossing improved the rate of success of interspecific crosses between common and tepary beans.…”
Section: The Use Of Interspecific Crosses To Develop Cultivars and Immentioning
confidence: 98%
See 1 more Smart Citation
“…Broughton et al (2003) suggested that molecular markers could be used to help reduce or remove barriers to inter-specific hybridization. Mejía-Jiménez et al (1994) reported that recurrent and congruity backcrossing improved the rate of success of interspecific crosses between common and tepary beans.…”
Section: The Use Of Interspecific Crosses To Develop Cultivars and Immentioning
confidence: 98%
“…Many pollinations are required to produce interspecific F 1 seed and this seed may require special treatment to produce plants (Freytag and Debouck 2002;Debouck 1991Debouck , 1999. Embryo rescue techniques are often needed to ensure the survival of interspecific F 1 hybrids (Mejía-Jiménez et al 1994). In addition, the choice of the common bean parent can affect the rate of success of the interspecific crosses.…”
Section: The Use Of Interspecific Crosses To Develop Cultivars and Immentioning
confidence: 99%
“…For this study 36 bush bean genotypes belonging to the Middle American gene pool were selected: twentytwo elite lines of common bean (BFS 10,BFS 29,BFS 32,BFS 67,MIB 778,NCB 226,NCB 280,RCB 273,RCB 593,SCR 16,SCR 2,SCR 9,SEN 56,SER 118,SER 119,SER 125,SER 16,SER 48,SER 78,SMC 141,SMC 43 and SXB 412); five interspecific lines between elite line SER 16 and Phaseolus coccineus (ALB 6, ALB 60, ALB 74, ALB 88 and ALB 213); one landrace of tepary bean (Phaseolus acutifolius) G 40001 from Veracruz-Mexico, and two interspecific lines between tepary bean and common bean (INB 841 and INB 827) developed from five cycles of congruity backcrossing of tepary with ICA Pijao (Mejía-Jiménez et al 1994). SEA 15 and BAT 477 were included as drought resistant checks, and three commercial cultivars of common bean (DOR 390, Pérola and Tio Canela) as drought sensitive materials.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Other studies of agriculturally relevant hybrids have found genotypic differences in the F 1 generation that carry over to the backcross/F 2 generation (e.g. beans: Mejia-Jimenez et al, 1994;Brassica: Roy, 1980).…”
Section: Fitness Variationmentioning
confidence: 99%